2008
DOI: 10.1196/annals.1417.003
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Signaling in the Dorsal Striatum Is Essential for Motivated Behaviors

Abstract: Genetically engineered mice that lack tyrosine hydroxylase in all dopaminergic neurons become hypoactive and aphagic and they starve by 4 weeks of age. However, they can be rescued by daily treatment with L-dopa, which restores activity and feeding for about 10 hours. Thus, these mice can be examined in both dopamine-depleted and dopamine replete states. A series of behavioral experiments lead to the primary conclusion that in the dopamine-depleted state these mice are not motivated to engage in goal-directed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
316
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 335 publications
(333 citation statements)
references
References 71 publications
(215 reference statements)
14
316
3
Order By: Relevance
“…However, motivation to engage in the tasks is significantly altered in these mice, suggesting that DA mediates ''wanting'' rewards, rather than learning (17). For example, DA-deficient mice appear to be unmotivated and will not engage in most tasks (49), whereas hyperdopaminergic mice perform some tasks more rapidly with less meandering, suggesting enhanced motivation (13). We observed longer latencies by the KO mice to make choices and engage in goal-directed behavior in many learning paradigms, suggesting that they may be less motivated in the absence of burst firing.…”
Section: Discussionmentioning
confidence: 99%
“…However, motivation to engage in the tasks is significantly altered in these mice, suggesting that DA mediates ''wanting'' rewards, rather than learning (17). For example, DA-deficient mice appear to be unmotivated and will not engage in most tasks (49), whereas hyperdopaminergic mice perform some tasks more rapidly with less meandering, suggesting enhanced motivation (13). We observed longer latencies by the KO mice to make choices and engage in goal-directed behavior in many learning paradigms, suggesting that they may be less motivated in the absence of burst firing.…”
Section: Discussionmentioning
confidence: 99%
“…DA is also involved with the motivation to perform behaviours necessary to procure and consume the food. In fact, DA-deficient mice are hypophagic, fail to engage in goaldirected feeding behaviours, and will die of starvation (Palmiter, 2008;Szczypka et al, 1999). Moreover, it was found that chemical lesions of the DA system (pharmacological antagonists of DA receptor), sufficient to inhibit food-seeking behaviour, did not affect the pleasure reactions to sucrose placed in the mouth (Berridge and Robinson, 1998;Tyrka et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…DA is also involved with the motivation to perform the behaviors necessary to procure and consume the food. In fact, Dopamine-deficient mice are hypophagic, fail to engage in goaldirected feeding behaviors, and will die of starvation (Szczypka et al, 1999;Palmiter, 2008). If DA signaling is restored only to the Cpu, mice will eat sufficiently for survival, whereas restoration of DA in the Nacc is not sufficient to sustain long-term feeding (Szczypka et al, 2001;Palmiter, 2008).…”
Section: Hypothalamic Sensing Of Lcfas and Metabolic Syndromementioning
confidence: 99%